Periodization of strength training for sports - Bompa, T. O.; Buzzichelli, C. A. (Human Kinetics, 2021)
Periodization of Strength Training for Sports demonstrates how to use periodized workouts to peak at optimal times by manipulating strength training variables through six training phases-anatomical adaptation, hypertrophy, maximum strength, conversion to specific strength, maintenance, and peaking. Part I. Foundations of Strength Training Chapter 1. Strength, Power, and Muscular Endurance in Sports Chapter 2. Neuromuscular Response to Strength Training Chapter 3. Laws and Principles of Strength Training for Sports